Dynamic response evaluation on TMD and main tower of Shanghai Tower subjected to Typhoon In‐Fa. (14th February 2022) - Zhang, Qilin; Luo, Xiaoqun; Ding, Jiemin; Xie, Bo; Gao, Xianzhan
Summary: Typhoon In‐Fa was the strongest tropical cyclone that impacted the Shanghai Tower (ST) since the completion of the Tower, which is the tallest building in China with a height of 632 m. Wind characteristics of the Typhoon In‐Fa were described based on measured data including average wind and fluctuating wind. Structural behaviors of the main tower and the tuned mass damper (TMD) during In‐Fa were measured and analyzed based on monitoring data from the structural health monitoring (SHM) system of the ST. The peak values and root mean squares (RMS) of accelerations and displacements of the TMD and main tower were evaluated and compared with numerical results. The correlations of accelerations and displacements between the TMD and the main tower were investigated, and linear relations would be given in a certain extent. Model parameters including fundamental frequencies and damping ratios were identified by the peak picking method, and strong linear correlations were obtained between the TMD and main tower. The results showed that the actual working behavior of the TMD meets the analyzed results, and the effectiveness of the vibration control of the TMD can be verified under strong winds near a 10‐year return period.